Platelet desialylation and TFH cells–the novel pathway of immune thrombocytopenia - Chen, Yuwen (Exp Hematol Oncol, 2021)
Immune thrombocytopenia (ITP) is an autoimmune disease characterized by immune-mediated destruction of one’s own platelets. The progression of thrombocytopenia involves an imbalance of platelet production and clearance. B cells can induce autoantibodies, and T cells contribute to the pathological progression as well. Some patients with ITP have a poor response to common first-line therapies. Recent studies have shown that a novel Fc-independent platelet clearance pathway is associated with poor prognosis in these patients. By this pathway, desialylated platelets can be cleared by Ashwell-Morell receptor (AMR) on hepatocytes. Research has demonstrated that patients with refractory ITP usually have a high level of desialylation, indicating the important role of sialylation on platelet membrane glycoprotein (GP) in patients with primary immune thrombocytopenia, and neuraminidase 1(NEU1) translocation might be involved in this process. Patients with ITP who are positive for anti-GPIbα antibodies have a poor prognosis, which indicates that anti-GPIbα antibodies are associated with this Fc-independent platelet clearance pathway. Experiments have proven that these antibodies could lead to the desialylation of GPs on platelets. The T follicular helper (TFH) cell level is related to the expression of the anti-GPIbα antibody, which indicates its role in the progression of desialylation. This review will discuss platelet clearance and production, especially the role of the anti-GPIbα antibody and desialylation in the pathophysiology of ITP and therapy for this disease.